High-grade chromium ore sand and production method thereof
By using chromium ore raw materials with low silica content, combined with spiral chutes, shaker and magnetic separation processes, the existing chromium ore sand production process is solved, and the efficient and low-cost production of high-grade chromium ore sand is achieved, which improves product stability and equipment life, and reduces environmental pollution.
Patent Information
- Application Number
- CN202510059138.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
AI Technical Summary
The existing high-grade chrome ore sand production process is complex, costly and has high environmental pressure, and silica impurities affect smelting stability and equipment life.
The chromium ore raw materials with low silica content are used to separate high-grade chromium ore sand through spiral chute or shaker reselecting technology and combined with magnetic separation technology to reduce production costs and environmental impact.
It realizes efficient production of high-grade chromium ore sand, improves the quality stability of ferrochromium, extends the service life of the equipment, reduces maintenance costs, and reduces environmental pollution.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mineral separation, in particular to high-grade chromium ore and a production method thereof. Background Art
[0002] Chromite, also known as chrome ore, is an equiaxed crystal system with octahedral crystals. Chromite has a semi-metallic luster, a Mohs hardness of 5.5, is brittle, and has a stable volume when heated. Its density depends on the spinel composition and the nature of the impurities, and is generally 4.2-4.8 g / cm 3 After mineral processing and screening to enrich chromium dioxide, it is often used as casting raw material, metallurgical raw material and refractory material.
[0003] Silicon dioxide is one of the common impurities in chromite. Under certain conditions, silicon dioxide will react with chromium and impurities in ferrochrome at high temperatures to form high-melting refractory materials, which will not only lead to corrosion and severe wear of furnace lining materials, increase equipment maintenance costs, but also have an adverse effect on the stability of the smelting process, thereby affecting the smelting process and smelting quality. Therefore, strictly controlling the content of silicon dioxide can not only help improve the quality stability of ferrochrome, but also reduce equipment corrosion and wear, and reduce equipment investment.
[0004] In the prior art, due to the embedded structural characteristics of chromite, a large amount of fine-grained minerals are easily produced during the grinding process, resulting in a relatively complex beneficiation process. It is usually necessary to use a variety of beneficiation methods (such as gravity separation, magnetic separation, flotation, etc.) in combination to obtain a more ideal chromium ore. A single beneficiation process is difficult to obtain satisfactory results. Therefore, the existing high-grade chromium ore production operation is complex, the process flow is cumbersome, the production cost is high, and a large amount of beneficiation wastewater is generated, which puts considerable pressure on the environment.
[0005] To this end, this application is filed. Summary of the invention
[0006] In view of the above-mentioned shortcomings of the prior art, the present invention provides a high-grade chromium ore and a production method thereof.
[0007] In order to achieve the above object, the main technical solutions adopted by the present invention include:
[0008] Firstly, the present invention provides a high-grade chromium ore, comprising the following components in mass percentage: Gr2O3 47.8%-60%, SiO2 0.01%-2%, Fe2O3 10%-29%, Al2O3 0.1%-16% and MgO 0.1%-20%.
[0009] The high-grade chromium ore proposed by the present invention has a very low silicon dioxide content and a very high chromium trioxide content. When used as a metallurgical raw material and refractory material, the amount of high-melting-point refractory materials formed under high temperature conditions is very small, so the quality stability of ferrochrome is high, and the corrosion and wear of equipment during the processing process are very slight, which prolongs the service life of the equipment and reduces the maintenance cost of the equipment. In addition, since silicon dioxide is a poor conductor of heat and has a relatively low melting point, the extremely low silicon dioxide content also helps to improve the thermal conductivity of the chromium ore and improve the overall refractory performance of the chromium ore.
[0010] Preferably, the components are included in the following mass percentages: Gr2O3 48%-51%, SiO2 0.5%-2%, Fe2O3 19%-27%, Al2O3 10%-15% and MgO 8%-12%.
[0011] When the components of the high-grade chromium ore meet the above requirements, its performance as a metallurgical raw material and refractory material is more excellent, and the difficulty of obtaining it is relatively small, and the production cost is low.
[0012] Secondly, the present invention proposes a production method for the above-mentioned high-grade chromium ore sand, which is obtained by processing the chromium ore raw material with a spiral chute and / or a shaking table as production equipment and adopting a gravity separation process. The chromium ore raw material has a particle size of 0.01-10 mm and includes the following components in mass percentage: Gr2O3 30%-55%, SiO2 2%-10%, Fe2O3 10%-35%, Al2O3 6%-20% and MgO6%-30%.
[0013] The applicant unexpectedly discovered that the chrome ore raw material with the above-mentioned components has particularly excellent dissociation properties, and the mineral particles are easily separated during the crushing and grinding process. It is speculated that this may be due to the uneven composition, the crystals of different components are twisted and cracked, and the component dissociation is formed. The chrome ore raw material with the above-mentioned components is not only easy to be crushed to form fine particles during the processing, but also when it is ground to a particle size of 0.01-10mm, a higher enrichment efficiency and better enrichment effect can be obtained by using a conventional gravity separation process.
[0014] Specifically, the principle of gravity separation is mainly based on the gravity separation of mineral particles under the combined action of mechanical shaking and water flushing. Gravity separation can significantly enrich chromium trioxide and reduce the content of silicon dioxide. The gravity separation process of the present invention is a conventional gravity separation process, which can adopt a spiral chute, a shaking table, or a combination of a spiral chute and a shaking table; gravity separation can be performed once, or the same gravity separation operation can be repeated multiple times without flotation, so the equipment investment is small, the energy consumption is low, the operation is simple, and the risk of environmental pollution is small.
[0015] Specifically, the chromium ore raw materials are firstly subjected to the gravity separation in the shaking table and then to the gravity separation in the spiral chute, and at least more than 50% of the chromium ore raw materials are materials with a particle size of 0.1-3 mm:
[0016] The specific operation of the shaking table gravity separation is: firstly, water is added to the chromium ore raw material to prepare a slurry with a solid content of 20%-45%, and then a shaking table is used for primary separation to obtain a primary concentrate, a primary ore mine and a primary tailings, and then water is added to the primary tailings to adjust its solid content to 15%-20% and then scavenged to obtain a scavenged concentrate, a scavenged ore mine and a scavenged tailings, and finally the primary concentrate and the scavenged concentrate are collected as intermediate products, and the primary tailings, the scavenged ore mine and the scavenged tailings are discarded, and the primary ore mine is further processed according to its grade and separation effect;
[0017] The specific operation of spiral chute gravity separation is: adopting a spiral chute to separate the intermediate product to obtain a spiral chute gravity separation rough concentrate and a spiral chute gravity separation tailings, grinding the spiral chute gravity separation tailings to a particle size not greater than 3mm and adopting a spiral chute to perform gravity separation again to obtain a spiral chute secondary gravity separation rough concentrate and a spiral chute secondary gravity separation tailings, and collecting the spiral chute gravity separation rough concentrate and the spiral chute secondary gravity separation rough concentrate as target products.
[0018] Through creative experiments, the present invention has found that when at least more than 50% of the chromium ore raw materials are materials with a particle size of 0.1-3 mm, the above-mentioned shaking table gravity separation is combined with the spiral chute gravity separation, and according to the above-mentioned specific operations, large-scale production of high-grade chromium ore sand can be achieved, and the production operation is relatively simple and the production cost is relatively low. More importantly, the enrichment efficiency of chromium trioxide is high and the enrichment effect is good.
[0019] It should be noted that in order to obtain a good scavenging effect, it is preferred to add water to the primary tailings during scavenging to reduce its solid content so that its solid content is not greater than the solid content during the primary selection on the shaking table.
[0020] Furthermore, after the shaking table gravity separation, the primary ore is first ground to make the material with a particle size of 0.1-3 mm exceed at least 50%, and then a second shaking table gravity separation is carried out and the concentrate obtained from the second shaking table gravity separation is collected as the intermediate product.
[0021] In the above embodiment, if the grade of the primary ore is high, it can be collected into the intermediate product. If the grade of the primary ore is low, it can be repeatedly re-selected on a shaking table after grinding to improve the enrichment efficiency, ensure the sorting accuracy, make full use of ore resources, reduce production costs, and improve economic benefits.
[0022] Thirdly, the present invention proposes another method for producing the above-mentioned high-grade chromium ore, which uses a magnetic separator as a production equipment and adopts a dry separation or wet separation process to process the chromium ore raw material to obtain it. The particle size of the chromium ore raw material is 0.01-10mm and includes the following components in mass percentage: Gr2O3 30%-55%, SiO2 2%-10%, Fe2O3 10%-35%, Al2O3 6%-20% and MgO6%-30%.
[0023] The principle of magnetic separation is mainly based on the attraction of magnetic field to different magnetically selected minerals. During the magnetic separation process, the magnetic system generates a strong magnetic field to attract and fix the magnetic particles on the drum or other magnetic elements of the magnetic separator, while the non-magnetic substances are discharged by the rotation of the drum, thereby achieving the separation of the ore. The present invention finds that the chromium ore raw material with a particle size of 0.01-10mm and including the following mass percentage components: Gr2O3 30%-55%, SiO2 2%-10%, Fe2O3 10%-35%, Al2O36%-20% and MgO 6%-30% can also obtain high-grade chromium ore sand through the magnetic separation process, and the enrichment efficiency and enrichment effect of the magnetic separation process are not inferior to the above-mentioned gravity separation process. More importantly, the production process is less, the operation is simpler, and the cost is lower.
[0024] Furthermore, when dry separation or wet separation is adopted, at least 50% of the chrome ore raw material is material with a particle size of 0.1-3 mm, and the magnetic field strength is not less than 4000 Gauss. It should be noted that magnetic separation can be performed once or multiple times.
[0025] When the raw material particle size is too large, some magnetic particles cannot be effectively captured during the magnetic separation process due to mutual interference between particles or limitations of the magnetic separation equipment; moreover, ore particles that are too large may more easily produce mechanical inclusions during the magnetic separation process, thereby reducing the magnetic separation efficiency. When the raw material particle size is too small, it may lead to magnetic agglomeration during the magnetic separation process, that is, multiple fine magnetic particles gather together to form larger agglomerates, thereby affecting the magnetic separation effect; moreover, fine-grained ore is also prone to form magnetic chains during the magnetic separation process, resulting in frequent blockage and wear problems during the magnetic separation process. The present invention finds that when at least more than 50% of the chromium ore raw material is material with a particle size of 0.1-3mm, the magnetic properties of the material can be fully exposed, the magnetic separation effect is optimal, and it is not easy to produce mechanical inclusions, magnetic agglomeration and magnetic chain phenomena during the magnetic separation process. The magnetic ore particles are more easily captured by the magnetic field of the magnetic separation equipment, thereby achieving efficient magnetic separation.
[0026] Furthermore, when the dry process is adopted, 60%-80% of the chromium ore raw material is material with a particle size of 0.1-3 mm. Before magnetic separation, the chromium ore raw material is first washed and dried, and then magnetically separated by a permanent magnetic separator or / and an electromagnetic magnetic separator with a magnetic field strength of 4600-9800 Gauss.
[0027] Furthermore, when the wet separation process is adopted, 70%-90% of the chrome ore raw material is a material with a particle size of 0.1-3 mm, the magnetic field strength is represented by H, the flushing water pressure is represented by P, and the water consumption per ton of the chrome ore raw material is represented by L. H, P, and L simultaneously satisfy: 8000 Gauss ≤ H ≤ 15000 Gauss, for example, H can be 8000 Gauss, 8100 Gauss, 8200 Gauss, 8300 Gauss, 8400 Gauss, Gaussian, 8500 Gaussian, 8600 Gaussian, 8700 Gaussian, 8800 Gaussian, 8900 Gaussian, 9000 Gaussian, 9100 Gaussian, 9200 Gaussian, 9300 Gaussian, 9400 Gaussian, 9500 Gaussian, 9600 Gaussian, 9700 Gaussian, 9800 Gaussian, 9900 Gaussian, 10000 Gaussian, 10100 Gaussian, 10200 Gaussian, 10300 Gaussian, 10400 Gaussian, 10500 Gaussian, 10600 Gaussian, 10700 Gaussian, 10800 Gaussian, 10900 Gaussian, 11000 Gaussian, 11100 Gaussian, 11200 Gaussian, 11300 Gaussian, 11400 Gaussian, 11500 Gaussian, 11600 Gaussian, 11700 Gaussian, 11800 Gaussian, 11900 Gaussian, 12000 Gaussian, 13000 Gaussian, 14000 Gaussian gauss, 15000 gauss, etc.; 12000Pa≤P≤18000Pa, for example, P can be 12000Pa, 12500Pa, 13000Pa, 13500Pa, 14000Pa, 14500Pa, 15000Pa, 15500Pa, 16000Pa, 16500Pa, 17000Pa, 17500Pa, 18000Pa, etc.; 0.4m 3 ≤L≤1.5m 3 , such as L can be 0.4m 3 、0.5m 3 、0.6m 3 、0.7m 3 、0.8m 3 、0.9m 3 , 1.0m 3 、1.1m 3 , 1.2m 3 , 1.3m 3 、1.4m 3 , 1.5m 3 .
[0028] In wet magnetic separation, magnetic field strength, flushing water pressure and water consumption per ton of chromium ore raw material are all key factors affecting the magnetic separation effect.
[0029] If the magnetic field strength is too large or too small, it may have an adverse effect on the magnetic separation effect. If the magnetic field strength is too large, the energy consumption of the magnetic separator will increase, which will not only increase the production cost, but also accelerate the wear of the equipment, and some non-magnetic or weakly magnetic particles may be mistakenly selected into the concentrate, resulting in a decrease in the purity of the concentrate; if the magnetic field strength is too small, the magnetic separator will weaken the adsorption capacity of magnetic particles, resulting in the inability to effectively recover some magnetic particles, which not only reduces the recovery rate of the concentrate, but also may cause a waste of resources; moreover, under a weak magnetic field, the boundary between magnetic particles and non-magnetic particles becomes blurred, making the separation effect worse, which may lead to an increase in the impurity content in the concentrate, affecting the quality and application value of the product.
[0030] The flushing water pressure should be kept within a certain range to ensure that the water flow speed inside the magnetic separator is moderate, so as to effectively flush out the non-magnetic particles, while not generating too strong a flushing force on the magnetic particles, thereby ensuring the magnetic separation effect. If the water pressure is too low, the water flow speed will be too slow, and the non-magnetic particles will not be flushed out in time, which will reduce the magnetic separation accuracy; if the water pressure is too high, it will increase the load on the magnetic separator, accelerate the wear of the equipment, and may lead to an increase in the loss of magnetic separation particles.
[0031] The amount of water used for flushing should be moderate to help the chrome ore raw materials disperse and suspend in the magnetic separator, increase their contact opportunities with the magnetic field, improve the efficiency of magnetic separation, and play the role of flushing and cooling equipment to extend the service life of the equipment. If the amount of flushing water is too much, it will increase the energy consumption and cost of subsequent treatment. If the amount of flushing water is too little, the chrome ore raw materials may not be fully dispersed and suspended, affecting the magnetic separation effect.
[0032] The present invention has been found through creative labor that when 70%-90% of the chromium ore raw materials are materials with a particle size of 0.1-3 mm, the magnetic separation is carried out according to the requirements of the above technical parameters, and the magnetic separation efficiency is high and the magnetic separation effect is good.
[0033] Furthermore, H, P, and L also satisfy the following relationship: 0.2≤2L-P / H≤0.8. Specifically, 2L-P / H can be 0.2, 0.23, 0.25, 0.28, 0.3, 0.32, 0.35, 0.37, 0.4, 0.43, 0.45, 0.48, 0.5, 0.53, 0.55, 0.58, 0.6, 0.62, 0.65, 0.67, 0.7, 0.72, 0.75, 0.78, 0.8, etc.
[0034] In order to determine the optimal relationship among the magnetic field intensity H, the flushing water pressure P, and the water consumption L per ton of the chrome ore raw material during wet magnetic separation, the present invention designs a number of experimental conditions, records the magnetic separation effect and the parameters such as the magnetic field intensity H, the flushing water pressure P, and the water consumption L per ton of the chrome ore raw material, and uses the statistical software SPSS to perform regression analysis on the collected data. The analysis shows that: when 2L-P / H is between 0.2 and 0.8, the magnetic separation effect is better, the content of chromium trioxide in the obtained chromite ore is significantly increased, and the content of silicon dioxide is significantly reduced, especially when 2L-P / H is 0.5, the magnetic separation effect is particularly good.
[0035] In the existing developed chromite ore, the content of chromium trioxide is very small above 47%. The present invention adopts chromium ore raw materials with specific composition and specific particle size, and can obtain high-grade chromium ore sand with chromium trioxide content of at least 47.8% by conventional gravity separation or magnetic separation process. The silicon dioxide content is very low, and it is a high-quality smelting raw material, refractory material and chemical raw material; the production method of high-grade chromium ore sand is conventional and relatively simple, with fewer process flows, simple production operations, low production costs and relatively environmental protection, so it has good application prospects and considerable economic benefits. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0037] The chromium ore raw material used in the following embodiments is imported from a chromite mine in Turkey. Ten batches of imported goods are randomly selected. After detection, the components are statistically composed, which include the following components in mass percentage: Gr2O3 20%-55%, SiO22%-10%, Fe2O3 10%-35%, Al2O36%-20% and MgO 6%-30%. Each batch of goods is selected from 100 kg, and after mixing evenly, it is further subjected to simple ore dressing to obtain coarse chromium ore sand, which includes the following components in mass percentage: including the following components in mass percentage: Gr2O3 30%-47%, SiO22.5%-4.3%, Fe2O3 10%-29%, Al2O3 6%-13% and MgO 6%-11%. The ore is crushed and graded to select products with particle sizes of 0.01-0.1 mm, 0.1-3 mm, and 3-10 mm. After mud washing and drying, the ore is combined and used as the processing raw material used in the following embodiments, i.e., chromium ore raw material.
[0038] When the products obtained in the following examples and comparative examples were tested, samples were taken three times, and the average value of the three tests was taken after the tests.
[0039] The technical details not described in detail in the following embodiments all adopt the existing technology.
[0040] Example 1
[0041] The composition of the processed raw materials is: 80wt% of 0.1-3mm products, 10wt% of 0.01-0.1mm products and 10wt% of 3-10mm products.
[0042] The specific process of gravity separation is: firstly gravity separation on a shaking table and then gravity separation on a spiral chute; firstly, water is added to the chromium ore raw material to prepare a slurry with a solid content of 30%, and then a shaking table is used for primary separation to obtain a primary concentrate, a primary ore mine and a primary tailings; then water is added to the primary tailings to adjust its solid content to 18% and then scavenging is performed to obtain a scavenged concentrate, a scavenged ore mine and a scavenged tailings; finally, the primary concentrate and the scavenged concentrate are collected as intermediate products, and the primary tailings, the scavenged ore mine and the scavenged tailings are discarded; the primary ore mine is first subjected to grinding treatment to make the material with a particle size of 0.1-3 mm reach 80%, and then a second shaking table gravity separation is performed and the concentrate obtained from the second shaking table gravity separation is classified as the intermediate product;
[0043] The specific operation of spiral chute gravity separation is: adopting a spiral chute to separate the intermediate product to obtain spiral chute gravity separation rough concentrate and spiral chute gravity separation tailings, grinding the spiral chute gravity separation tailings to a material with a particle size of 0.1-3mm to reach 80% and adopting a spiral chute to perform gravity separation again to obtain spiral chute secondary gravity separation rough concentrate and spiral chute secondary gravity separation tailings, and collecting the spiral chute gravity separation rough concentrate and the spiral chute secondary gravity separation rough concentrate as target products.
[0044] The target product includes the following components in mass percentage: Gr2O3 52%, SiO2 1.2%, Fe2O3 23%, Al2O3 10%, MgO 13.5% and other 0.3%.
[0045] Example 2
[0046] Compared with Example 1, the composition of the processed raw materials is adjusted to: 70wt% of 0.1-3mm products, 20wt% of 0.01-0.1mm products and 10wt% of 3-10mm products. The primary ore selection is firstly subjected to grinding treatment, so that the material with a particle size of 0.1-3mm reaches 70%, and the spiral chute gravity selection tailings are ground to a material with a particle size of 0.1-3mm reaches 70% and the spiral chute is used for gravity selection again. The rest is consistent with Example 1.
[0047] The target product includes the following components in mass percentage: Gr2O3 50%, SiO2 1.5%, Fe2O3 22%, Al2O3 11%, MgO 15% and other 0.5%.
[0048] Example 3
[0049] Compared with Example 1, the composition of the processed raw materials is adjusted to: 60wt% of 0.1-3mm products, 20wt% of 0.01-0.1mm products and 20wt% of 3-10mm products. The primary ore selection is firstly subjected to grinding treatment, so that the material with a particle size of 0.1-3mm reaches 60%, and the spiral chute gravity separation tailings are ground to a material with a particle size of 0.1-3mm reaches 60% and the spiral chute is used for gravity separation again. The rest is consistent with Example 1.
[0050] The target product includes the following components in mass percentage: Gr2O3 49%, SiO2 1.8%, Fe2O3 21%, Al2O3 13%, MgO 15% and other 0.2%.
[0051] Example 4
[0052] Compared with Example 1, the composition of the processed raw materials is adjusted to: 50wt% of 0.1-3mm products, 20wt% of 0.01-0.1mm products and 30wt% of 3-10mm products. The primary ore selection is firstly subjected to grinding treatment to make the material with a particle size of 0.1-3mm reach 50%, the spiral chute gravity separation tailings are ground to a material with a particle size of 0.1-3mm reach 50% and the spiral chute is used for gravity separation again. The rest is consistent with Example 1.
[0053] The target product includes the following components in mass percentage: Gr2O3 47.8%, SiO2 2%, Fe2O3 21.5%, Al2O3 11.3%, MgO 17% and other 0.4%.
[0054] It can be seen from the product compositions of Examples 1 to 4 that high-grade chromium ore can be obtained by conventional gravity separation process using the processing raw materials defined in the present invention. Moreover, the greater the proportion of 0.1-3 mm products, the better the gravity separation effect is, and the content of silicon dioxide is significantly reduced. The reason for this should be that when the particle size is 0.1-3 mm, the density difference between the target component and the impurity component is more significant, which is conducive to the effective separation of the impurity component, making the separation more thorough and the separation accuracy higher.
[0055] Example 5
[0056] Compared with Example 1, before the primary selection on the shaking table, water is first added to the chromium ore raw material to prepare a slurry with a solid content of 20%; before the scavenging, water is added to the primary selection tailings to adjust its solid content to 20% before scavenging. The rest is consistent with Example 1.
[0057] The target product includes the following components in mass percentage: Gr2O3 50%, SiO2 1.7%, Fe2O3 24%, Al2O3 9%, MgO 14.7% and other 0.6%.
[0058] Example 6
[0059] Compared with Example 1, before the primary selection on the shaking table, water is first added to the chromium ore raw material to prepare a slurry with a solid content of 45%; before the scavenging selection, water is added to the primary selection tailings to adjust its solid content to 15% before scavenging selection. The rest is consistent with Example 1.
[0060] The target product includes the following components in mass percentage: Gr2O3 49.2%, SiO2 1.3%, Fe2O3 21.5%, Al2O3 12%, MgO 15.8% and other 0.2%.
[0061] It can be seen from the product compositions of Example 1, Example 5 and Example 6 that high-grade chromium ore can be obtained by using the gravity separation process technical parameters defined in the present invention. Reasonably increasing the difference in solid content between the shaking table primary separation slurry and the scavenging separation slurry helps to reduce the content of silicon dioxide, making the separation of silicon dioxide more thorough.
[0062] Example 7
[0063] The dry magnetic separation process is adopted, and the composition of the processed raw materials is: 70wt% of 0.1-3mm products, 10wt% of 0.01-0.1mm products and 20wt% of 3-10mm products. Before magnetic separation, the above-mentioned processed raw materials are washed and dried again. During magnetic separation, a permanent magnetic separator with a magnetic field strength of 6800 Gauss is used.
[0064] Example 8
[0065] Compared with Example 7, the composition of the processed raw materials was adjusted to: 60 wt% of 0.1-3 mm product, 20 wt% of 0.01-0.1 mm product and 20 wt% of 3-10 mm product. The rest was the same as Example 7.
[0066] Example 9
[0067] Compared with Example 7, the composition of the processed raw materials was adjusted to: 80 wt% of 0.1-3 mm product, 10 wt% of 0.01-0.1 mm product and 10 wt% of 3-10 mm product. The rest was the same as Example 7.
[0068] Example 10
[0069] Compared with Example 7, the magnetic field strength of the magnetic separation is adjusted to 4600 Gauss. The rest is the same as Example 1.
[0070] Embodiment 11
[0071] Compared with Example 7, the magnetic field strength of the magnetic separation is adjusted to 9800 Gauss. The rest is the same as Example 1.
[0072] After testing, the products obtained in Examples 7 to 11 had a Gr2O3 content of 48%-52% and a SiO2 content of 0.8%-1.4%.
[0073] Example 12-Example 15
[0074] The wet magnetic separation process is adopted, and the composition of the processed raw materials is: 80wt% of 0.1-3mm, 10wt% of 0.01-0.1mm products and 10wt% of 3-10mm products. Before magnetic separation, the above-mentioned processed raw materials are washed and dried again. During magnetic separation, the magnetic field intensity H, the flushing water pressure P, the water consumption per ton of raw materials L, 2L-P / H and the Gr2O3, Fe2O3, SiO2 and the like in the final product are specifically shown in Table 1.
[0075] project P H L 2L-P / H <![CDATA[Gr2O3]]> <![CDATA[Fe2O3]]> <![CDATA[SiO2 <!-- 6 -->]]> Example 12 12000 12000 0.6 0.2 49.8 21.6 1.3 Example 13 13000 10000 0.8 0.3 52 21 0.7 Embodiment 14 16000 10700 1 0.5 53 19 0.5 Embodiment 15 18000 11250 1.2 0.8 50 20 0.9 Example 16 16000 10700 1 0.5 51 22 5.6 Embodiment 17 16000 10700 1 0.5 52 23 6.2 Embodiment 18 16000 10700 1 0.5 61 11 0.3 Comparative Example 3 16150 9500 0.9 0.1 53 27 4.2 Comparative Example 4 18000 9500 1.4 0.9 45.9 23 4.6 Comparative Example 5 12000 12000 1 1 44 25 5.8 Comparative Example 6 16000 10700 1 0.5 42 25 8.4 Comparative Example 7 16000 10700 1 0.5 39 24 9.5
[0076] As shown in Table 1: From the test results of Example 12 to Example 15, it can be seen that under the wet magnetic separation process parameters specified in the present invention, the obtained product has a high grade, the chromium trioxide content is significantly increased, and the silicon dioxide content is significantly reduced, which far exceeds the relevant requirements for refractory materials.
[0077] Example 16
[0078] The wet magnetic separation process was adopted, and the process parameters were the same as those in Example 14, but the composition of the processed raw materials was adjusted, specifically: the composition of the processed raw materials was: 70wt% of 0.1-3mm, 10wt% of 0.01-0.1mm products, and 20wt% of 3-10mm products. The test results are shown in Table 1.
[0079] Embodiment 17
[0080] The wet magnetic separation process was adopted, and the process parameters were the same as those in Example 14, but the composition of the processed raw materials was adjusted, specifically: the composition of the processed raw materials was: 90wt% of 0.1-3mm, 5wt% of 0.01-0.1mm products, and 5wt% of 3-10mm products. The test results are shown in Table 1.
[0081] Embodiment 18
[0082] The same processing materials and processing technology as in Example 14 were used, and the number of magnetic separations was increased from 1 to 5. The test results are shown in Table 1.
[0083] Comparative Example 1
[0084] Compared with Example 1, the composition of the processed raw materials is adjusted to: 40wt% of 0.1-3mm products, 30wt% of 0.01-0.1mm products and 30wt% of 3-10mm products. The primary ore selection is firstly subjected to grinding treatment, so that the material with a particle size of 0.1-3mm reaches 40%, and the spiral chute gravity selection tailings are ground to a material with a particle size of 0.1-3mm reaches 40% and the spiral chute is used for gravity selection again. The rest is consistent with Example 1.
[0085] The target product includes the following components in mass percentage: Gr2O3 45%, SiO2 4.5%, Fe2O3 23%, Al2O3 15.3%, MgO 12% and other 0.2%.
[0086] Compared with Example 1 to Example 4, it can be seen that when the 0.1-3 mm material in the processed raw material is less than 50%, although the chromium trioxide content in the target product is relatively high, the impurity silicon dioxide is not separated completely and does not meet the use requirements of the refractory material.
[0087] Comparative Example 2
[0088] Compared with Example 1, before the primary selection on the shaking table, water is first added to the chromium ore raw material to prepare a slurry with a solid content of 50%; before the scavenging selection, water is added to the primary selection tailings to adjust its solid content to 25% before scavenging selection. The rest is consistent with Example 1.
[0089] The target product includes the following components in mass percentage: Gr2O3 43%, SiO2 5.6%, Fe2O3 24.3%, Al2O3 14%, MgO 12.7% and other 0.4%.
[0090] Compared with Example 1, Example 5 and Example 6, it can be seen that when the solid content of the shaking table primary separation pulp and the scavenging separation pulp is relatively high, it is not conducive to re-selection, and the resulting product has a high silica content and poor performance, and cannot meet the use requirements of refractory materials.
[0091] Comparative Example 3-Comparative Example 5
[0092] A wet magnetic separation process was adopted, and the composition of the processed raw materials was the same as that in Example 12, but the specific technical parameters were adjusted, as shown in Table 1.
[0093] From the comparison of the test results of Comparative Examples 3, 4, 5 and Example 12, it can be seen that: when the magnetic field intensity H, the flushing water pressure P, and the water consumption per ton of raw material L are all within the required range, but 2L-P / H does not meet the requirements, the chromium trioxide enrichment effect in the product becomes worse and the content of impurity silicon dioxide increases.
[0094] Comparative Example 6
[0095] The wet magnetic separation process was adopted, and the process parameters were the same as those in Example 14, but the composition of the processed raw materials was adjusted, specifically: the composition of the processed raw materials was: 0.1-3mm 60wt%, 0.01-0.1mm product 20wt% and 3-10mm product 20wt%. The test results are shown in Table 1.
[0096] Comparative Example 7
[0097] The wet magnetic separation process was adopted, and the process parameters were the same as those in Example 14, but the composition of the processed raw materials was adjusted, specifically: the composition of the processed raw materials was: 0.1-3 mm 50 wt%, 0.01-0.1 mm product 20 wt% and 3-10 mm product 30 wt%. The test results are shown in Table 1.
[0098] From the comparison of Comparative Examples 6 and 7 with Example 14, it can be seen that a moderate particle size distribution of the processed raw materials is helpful to improve the chromium trioxide enrichment effect and reduce the content of impurity silicon dioxide. If the particle size distribution of the raw materials is inappropriate, the obtained product cannot meet the use requirements of the refractory material.
[0099] Comparative Example 8
[0100] A wet magnetic separation process was adopted, and the process parameters were the same as those in Example 14, but the processing raw materials were imported from a mine in South Africa. The composition of the processing raw materials was the same as that in Example 14, but the components were different, including the following components in mass percentage: Gr2O3 40.45%-47%, SiO2 5%-7.4%, Fe2O3 26%-29%, Al2O3 14.62%-15% and MgO 11.24%-12.0%.
[0101] The target product includes the following components in mass percentage: Gr2O3 47.5%, SiO2 4.2%, Fe2O3 24.5%, Al2O3 9.5%, MgO 10.3% and other 4%. Obviously, the magnetic separation effect of the processed raw material is obviously inferior to that of the raw material used in the present invention.
[0102] Although the embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and cannot be understood as limiting the present invention. Those skilled in the art may change, modify, replace and deform the above embodiments within the scope of the present invention. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.
Claims
1. A high-grade chromium ore, characterized in that: The invention comprises the following components in mass percentage: Gr2O3 47.8%-60%, SiO2 0.01%-2%, Fe2O3 10%-29%, Al2O3 0.1%-16% and MgO 0.1%-20%.
2. The high-grade chromium ore according to claim 1, characterized in that: The invention comprises the following components in mass percentage: Gr2O3 48%-51%, SiO2 0.5%-2%, Fe2O3 19%-27%, Al2O3 10%-15% and MgO 8%-12%.
3. A method for producing high-grade chromium ore according to claim 1 or 2, characterized in that: The chromium ore raw material is obtained by processing the chromium ore raw material with a spiral chute or / and a shaking table as production equipment through a gravity separation process. The chromium ore raw material has a particle size of 0.01-10 mm and includes the following components in mass percentage: Gr2O3 30%-55%, SiO2 2%-10%, Fe2O3 10%-35%, Al2O3 6%-20% and MgO 6%-30%.
4. The method for producing high-grade chromium ore according to claim 3, characterized in that: Firstly, the chromium ore is re-selected by a shaking table and then by a spiral chute. At least 50% of the chromium ore raw materials are materials with a particle size of 0.1-3 mm. The specific operation of the shaking table gravity separation is: firstly, water is added to the chromium ore raw material to prepare a slurry with a solid content of 20%-45%, and then a shaking table is used for primary separation to obtain a primary concentrate, a primary ore mine and a primary tailings, and then water is added to the primary tailings to adjust its solid content to 15%-20% and then scavenged to obtain a scavenged concentrate, a scavenged ore mine and a scavenged tailings, and finally the primary concentrate and the scavenged concentrate are collected as intermediate products, and the primary tailings, the scavenged ore mine and the scavenged tailings are discarded, and the primary ore mine is further processed according to its grade and separation effect; The specific operation of spiral chute gravity separation is: adopting a spiral chute to separate the intermediate product to obtain a spiral chute gravity separation rough concentrate and a spiral chute gravity separation tailings, grinding the spiral chute gravity separation tailings to a particle size not greater than 3mm and adopting a spiral chute to perform gravity separation again to obtain a spiral chute secondary gravity separation rough concentrate and a spiral chute secondary gravity separation tailings, and collecting the spiral chute gravity separation rough concentrate and the spiral chute secondary gravity separation rough concentrate as target products.
5. The method for producing high-grade chromium ore according to claim 4, characterized in that: After the shaking table gravity separation, the primary ore is firstly ground to make the material with a particle size of 0.1-3 mm exceed 50% at least, and then the second shaking table gravity separation is carried out and the concentrate obtained by the second shaking table gravity separation is collected as the intermediate product.
6. A method for producing high-grade chromium ore according to claim 1 or 2, characterized in that: The chromium ore raw material is obtained by using a magnetic separator as production equipment and a dry or wet separation process. The chromium ore raw material has a particle size of 0.01-10 mm and includes the following components in mass percentage: Gr2O3 30%-55%, SiO2 2%-10%, Fe2O3 10%-35%, Al2O3 6%-20% and MgO 6%-30%.
7. The method for producing high-grade chromium ore according to claim 6, characterized in that: When the dry or wet separation process is adopted, at least more than 50% of the chromium ore raw materials are materials with a particle size of 0.1-3 mm, and the magnetic field strength is not less than 4000 Gauss.
8. The method for producing high-grade chromium ore according to claim 7, characterized in that: When the dry process is adopted, 60%-80% of the chromium ore raw material is material with a particle size of 0.1-3 mm. Before magnetic separation, the chromium ore raw material is first washed and dried, and then magnetically separated by a permanent magnetic separator or / and an electromagnetic magnetic separator with a magnetic field strength of 4600-9800 Gauss.
9. The method for producing high-grade chromium ore according to claim 7, characterized in that: When the wet separation process is adopted, 70%-90% of the chromium ore raw material is a material with a particle size of 0.1-3 mm, the magnetic field strength is represented by H, the flushing water pressure is represented by P, and the water consumption per ton of the chromium ore raw material is represented by L. H, P, and L simultaneously meet the following conditions: 8000 Gauss ≤ H ≤ 15000 Gauss, 12000 Pa ≤ P ≤ 18000 Pa, 0.4 m 3 ≤L≤1.5m 3 .
10. The method for producing high-grade chromium ore according to claim 9, characterized in that: H, P, and L also satisfy the following relationship: 0.2≤2L-P / H≤0.8.
Citation Information
Patent Citations
Method for separating chromium and iron in ferrochrome placer deposits through magnetizing roasting
CN103589859A
Novel beneficiation technology of high-grade ferrochrome ore
CN103878111A
Beneficiation method for stepped recovery and segmented tailing discarding of low-grade chromite ore
WO2023060890A1